Motivation And Product Knowledge In Islamic Banking: A Literature Review On Student Saving Interest - Khusnul Khatimah; Yancis Yancis; Syaripuddin Syaripuddin; Ermiati Ermiati (AL HILALI: Jurnal Perbankan dan Ekonomi Islam, 2026)
This study aims to analyze the influence of motivation and knowledge of Islamic banking product variations on students’ interest in saving, through a systematic literature review approach. The phenomenon of low interest in saving among students at Islamic higher education institutions, particularly in the context of Bank Syariah Indonesia (BSI), has become an important concern in efforts to increase financial inclusion and Islamic financial literacy. The method used is a literature review, by collecting, analyzing, and synthesizing relevant academic sources including journals, theses, and books published in the last ten years. The results of the literature review show that: (1) motivation, both intrinsic and extrinsic, has a significant positive effect on students’ interest in saving at Islamic banks; (2) knowledge of product variations in Islamic banking, including understanding of contracts, profit-sharing systems, and digital services, is also proven to significantly increase students’ interest in saving; (3) simultaneously, motivation and product knowledge together form a strong predictor of students’ saving interest. These findings are in line with various previous empirical studies and reinforce the importance of educational strategies and Islamic financial literacy to strengthen students’ saving behavior. This article provides theoretical and practical implications for Islamic banking institutions, Islamic higher education, and future researchers.